Основні завдання сучасної професійної освіти в галузі туризму - Біда Олена; Орос Ільдіко; Бжежіньска Рената; Bida Olena; Orosz Ildikó; Brzezinska Renata; Oros Ildiko; Brzezińska Renata (РВВ ЦДПУ ім. В. Винниченка, 2018)
Резюме. У статті з’ясовано, що першочерговою проблемою у сучасній педагогіці є проблема мотивації навчання. Виокремлено компоненти компетентності майбутніх фахівців галузі туризму. Розкрито три аспекти підготовки фахівців, що важливі для будь-якої сфери туризму (фундаментальне навчання, технічне навчання, особисті здібності).

Abstract. The article found that the primary problem in modern pedagogy is the problem of teaching motivation. The components of competence of the future specialists of the tourism industry are singled out. Three aspects of the training of specialists are revealed, which are important for any sphere of tourism (fundamental education, technical training, personal abilities). The main tasks of modern professional education in the field of tourism can be considered: providing fundamental scientific, professional and practical training in the field of tourism; obtaining students knowledge and skills of educational and qualification levels in accordance with their vocation, interests and abilities; improvement of scientific and professional training of personnel for the tourism industry. The general pedagogical principles underlying the formation of the content of professional tourism education are clarified. The use of new technologies helps to improve the level of training of future specialists in the tourism industry. In the process of such organization of educational activity, students are convinced of the need for knowledge and their effectiveness, learn to compare, generalize, classify, establish cause-effect relationships, express thoughts, defend their point of view, ensure success in training, and develop professional competence.

Резюме. В статье установлено, что первоочередной проблемой в современной педагогике проблема мотивации учения. Выделены компоненты компетентности будущих специалистов отрасли туризма. Раскрыто три аспекта подготовки специалистов, которые важны для любой сферы туризма (фундаментальное обучение, техническое обучение, личные способности).
Main objectives of modern professional education in the field of tourism
Keywords: майбутні фахівці; галузь туризму; формування змісту професійної туристської освіти; удосконалення наукової і професійної підготовки кадрів; формування змісту професійної туристської освіти